(untitled) (Revista de Ciências Agroveterinárias, 2023)
Innovation platforms (IP) have become a recognized approach to analyze agricultural and agro-industrial value chains, since they allow the interpretation of broad factors that complement aspects of production, such as innovation capacities and systemic problems. However, one of the important challenges of IP is also its analysis at various geographical scales. Therefore the goal is analyze innovation platform IP for the development of dairy activity performance at the regional level, in order to reveal restrictions, challenges and opportunities towards a greater understanding and strengthening the dairy chain in Colombia. Information was collected through a web survey to stakeholders, reaching the response of 40 of them. However, for actors mapping, two interviews were previously conducted with key actors in the region. Additionally, a complementary secondary information review was carried out. It was found that the institutional relationship as a systemic problem mainly limits the performance of the individual, organizational and political capacities of the actors. On the other hand, the local actors presence and regulations limit projection and network capacities, respectively. In turn, there are some differences between the self-assessment of capacities and the external assessment of an actor towards others, which may have implications for perceived legitimacy for certain institutional arrangements and governance of relationships. Finally the integrated framework of performance analysis of the IP for the development of the dairy chain at the regional level, reveals differences in the evaluation of the capacities of the actors, as well as the existence of systemic problems that limit the capacities of the actors in the individual, organization, projection, network and political levels